Quantitative Analysis of Tumor Response Using Advanced PET/CT Imaging Modalities - Musa, Ahmed Hashim Issa; ktab, Muntazr Mukhls AbdAlhusien; Madhboub, Zaid Razak Musa; Arar, Mortada Lafta Hussein; lafta, Tahsin Abdullah mansi (American Journal of Botany and Bioengineering, 2024)
In the field of oncology, cross-sectional imaging has undergone a monumental shift in the paradigm of diagnosis and monitoring response to therapy in patients affected by solid tumors. Over the years, the evolution of FDG PET (Fluorodeoxyglucose Positron Emission Tomography) has revolutionized the way we evaluate and manage these patients.